The Effect of Operating Condition on Low Pressure Steam (LPS) in Sugar Factory by Pinch Analysis - Riadi, Indra; Puji Utomo, Dani (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
In the present work the sugar plant in Sragen, Central Java, Indonesia has ten evaporators that can be configured to five effect evaporators. The optimization ofenergy demand, finding optimum operating condition of LowPressure Steam (LPS), and choosing the best configuration of multiple effect evaporator (MEE) were performed by pinch analysis. In this paper, LPS at 0.4 kg/cm2.G – 1.1 kg/cm2.G were evaluated. The results show that the optimum operating condition of LPS was at 0.9 kg/cm2.G – 1.1 kg/cm2.G. This optimum operating condition enhances the energy saving by about 30% compared to that of existing plant (0.4 kg/cm2.G). The best performance value that can be achieved were Steam on Cane (SOC) by 43.50% and Steam Economy (SE) by 2.1